Relationship between seismicity and active faults in Thanh Hoa province detected by local seismic network - N., Duong T.; Phong, Lai Hop; N., Pham D.; H., Chen C.; T., Dinh V. (Vietnam Journal of Earth Sciences, 2021)
Thanh Hoa province belongs to the southwest part of Northwest Vietnam, which is considered a tectonically active region. In the area of Thanh Hoa province, there are three deep-seated tectonic faults, namely Son La-Bim Son, Song Ma, and Sop Cop. As predicted by scientists, these faults are capable of producing credible earthquakes that might be the strongest in the territory of Vietnam. Besides the three main seismogenic sources, in the province, there are other smaller active faults such as Thuong Xuan-Ba Thuoc and Thuong Xuan-Vinh Loc but the relationship of these faults with seismic activity is still rather blurred. This may due to the sparseness of the Vietnamese National Seismic Network which can not record adequately small earthquakes in the area. This paper presents new results of additional monitoring from a local seismic network using 12 Guralp - 6TD broadband seismometers that have been deployed in Thanh Hoa province since November 2009. We found that the Thanh Hoa area is not seismically quiet. The average number of earthquakes recorded by the network has reached 80 - 90 events per year and some of them have magnitude from ML 3.0 to 4.0. By integration of the earthquake epicenters derived from the local network and distribution of active faults, we can detect several earthquakes locating near the three active faults, not only along the main faults but also along its subsidiary faults. We focused on the active faults of Thuong Xuan-Ba Thuoc and Thuong Xuan-Vinh Loc by using the recent results of the gravity, seismic, and magnetotelluric data analyses. Several recorded earthquakes distribute along the two small faults and some of them reach magnitude 3.0 or greater on the ML scale. In this study, the Thuong Xuan-Vinh Loc is recognized as a seismogenic source. To identify seismic hazard potential caused by earthquakes generated from the active faults, segmentation of the Thuong Xuan - Ba Thuoc fault had been done based on geological and geomorphological indications and seismic activity, and then the peak ground acceleration was determined for each fault segment. Besides, a large number of earthquake epicenters do not have a good correlation with a specific fault, especially in the area of Thanh Hoa coastal plain, which is covered by thick layers of Neogene - Quaternary sediment. This shows that there may be hidden active faults in the area which are needed to study further.